The development of the basketball player's tactical thinking during the starting - Kovalenko O. P.; Zakharina E. A. (Kharkov National Pedagogical University, 2011)
The scientific research results were analyzed connected with tactical and operating thinking of the young sportswoman. In experiment took part children at the age of 10-12 years old. It is used mathematical test from 40 examples. The index of the concentration was determined. The quantity of the turnover (tackling) by the players during the control game was analyzed. The examples of the tactical movement's scheme during the educational and work-out session are presented in the article. It is proposed to use tactical tasks, which include to make an addition for the short time.